Screening and Characterization of Reactive Compounds with In Vitro Peptide-Trapping and Liquid Chromatography/High-Resolution Accurate Mass Spectrometry. (February 2014) - Wei, Cong; Chupak, Louis S.; Philip, Thomas; Johnson, Benjamin M.; Gentles, Robert; Drexler, Dieter M.
The present study describes a novel methodology for the detection of reactive compounds using in vitro peptide-trapping and liquid chromatography–high-resolution accurate mass spectrometry (LC-HRMS). Compounds that contain electrophilic groups can covalently bind to nucleophilic moieties in proteins and form adducts. Such adducts are thought to be associated with drug-mediated toxicity and therefore represent potential liabilities in drug discovery programs. In addition, reactive compounds identified in biological screening can be associated with data that can be misinterpreted if the reactive nature of the compound is not appreciated. In this work, to facilitate the triage of hits from high-throughput screening (HTS), a novel assay was developed to monitor the formation of covalent peptide adducts by compounds suspected to be chemically reactive. The assay consists of in vitro incubations of test compounds (under conditions of physiological pH) with synthetically prepared peptides presenting a variety of nucleophilic moieties such as cysteine, lysine, histidine, arginine, serine, and tyrosine. Reaction mixtures were analyzed using full-scan LC-HRMS, the data were interrogated using postacquisition data mining, and modified amino acids were identified by subsequent LC-HRMS/mass spectrometry. The study demonstrated that in vitro nucleophilic peptide trapping followed by LC-HRMS analysis is a useful approach for screening of intrinsically reactive compounds identified from HTS exercises, which are then removed from follow-up processes, thus obviating the generation of data from biochemical activity assays.